THE EFFECT OF REGIONAL FINANCIAL EFFICIENCY LEVEL ON BUDGET PERFORMANCE OF REGIONAL ORIGINAL INCOME IN PAREPARE CITY FOR 2014-2018 PERIOD - Yadi Arodhiskara; Muhammad Hatta; Ariana Ariana (Journal AK-99, 2022)
This study aims to determine the effect of regional financial efficiency level on the budget performance inRegional Original Income in the City of Parepare for 2014-2018 period. The data collection techniques used in this study are observation and documentation. The subjects in this study were the research samples, namely the regional financial documents of Parepare City for 2014-2018 period. This study uses quantitative analysis. The results of the study concluded that: regional financial efficiency affects the budget performance of Regional Original Income in Parepare City. Regional financial efficiency for 2014 – 2018 period, the successive valuesare: 15.20%,17.24%, 14.67%, 13.07% and 12.82%. Meanwhile, the budget performance of Regional Original Income as measured based on the effectiveness ratio for 2014 - 2018 period, the valueswere: 130.12%, 94.42%, 98.77%, 99.74% and 89.07%. Both of these ratios depend on the realization of Original Regional Income received by the regions.